Changes in Children's Body Composition and Posture during Puberty Growth - Wojciech Rusek; Joanna Baran; Justyna Leszczak; Marzena Adamczyk; Rafał Baran; Aneta Weres; Grzegorz Inglot; Ewelina Czenczek-Lewandowska; Teresa Pop (MDPI AG, 2021)
The main goal of our study was to determine how the age of children, puberty and anthropometric parameters affect the formation of body composition and faulty body posture development in children. The secondary goal was to determine in which body segments abnormalities most often occur and how gender differentiates the occurrence of adverse changes in children's body posture and body composition during puberty. The study group consisted of 464 schoolchildren aged from 6-16. Body posture was assessed with the Zebris system. The composition of the body mass was tested with Tanita MC 780 MA body mass analyzer and the body height was measured using a portable stadiometer PORTSTAND 210. The participants were further divided due to the age of puberty. Tanner division was adopted. The cut-off age for girls is ≥10 years and for boys it is ≥12 years. The analyses applied descriptive statistics, the Pearson correlation, stepwise regression analysis and the t-test. The accepted level of significance was p < 0.05. The pelvic obliquity was lower in older children (beta = −0.15). We also see that age played a significant role in the difference in the height of the right pelvis (beta = −0.28), and the difference in the height of the right shoulder (beta = 0.23). Regression analysis showed that the content of adipose tissue (FAT%) increased with body mass index (BMI) and decreased with increasing weight, age, and height. Moreover, the FAT% was lower in boys than in girls (beta negative equal to −0.39). It turned out that older children (puberty), had greater asymmetry in the right shoulder blade (p < 0.001) and right shoulder (p = 0.003). On the other hand, younger children (who were still before puberty) had greater anomalies in the left trunk inclination (p = 0.048) as well as in the pelvic obliquity (p = 0.008). Girls in puberty were characterized by greater asymmetry on the right side, including the shoulders (p = 0.001), the scapula (p = 0.001) and the pelvis (p < 0.001). In boys, the problem related only to the asymmetry of the shoulder blades (p < 0.001). Girls were characterized by a greater increase in adipose tissue and boys by muscle tissue. Significant differences also appeared in the body posture of the examined children. Greater asymmetry within scapulas and shoulders were seen in children during puberty. Therefore, a growing child should be closely monitored to protect them from the adverse consequences of poor posture or excessive accumulation of adipose tissue in the body.